Outcome of Severe Bacterial Pneumonia in the Era of Pneumococcal Vaccination - del Rosal, Teresa; Caminoa, María Belén; González-Guerrero, Alba; Falces-Romero, Iker; Romero-Gómez, María Pilar; Baquero-Artigao, Fernando; Sainz, Talía; Méndez-Echevarría, Ana; Escosa-García, Luis; Aracil, Francisco Javier; Calvo, Cristina (Frontiers in Pediatrics, 2020)
Introduction. After the introduction of pneumococcal conjugate vaccines, community-acquired pneumonia (CAP) caused by Streptococcus pneumoniae has decreased whereas Staphylococcus aureus and Streptococcus pyogenes could be increasing. These bacteria have been associated with high rates of complications. Aims. (1) To describe the characteristics of pediatric bacterial CAP requiring hospitalization. (2) To compare outcomes according to causative microorganisms. (3) To analyze changes in bacterial CAP rate and etiology over time. Patients and methods. Retrospective single-center study of inpatients aged 1 month-16 years with culture-confirmed bacterial CAP in 2010-2018 in Madrid, Spain. Results. We included 64 cases (42 S. pneumoniae, 13 S. pyogenes and 9 S. aureus). Culture-confirmed CAP represented 1.48-2.33/1,000 all-cause pediatric hospital admissions, and its rate did not vary over time. However, There was a significant decrease in pneumococcal CAP in the last three years of the study (78% of CAP in 2010-2015 vs. 48% in 2016-18, p=0.017). Median hospital stay was 10.5 days (interquartile range 5-19.5), 38 patients (59%) developed complications and 28 (44%) were admitted to the intensive care unit. Outcomes were similar among children with S. pneumoniae and S. aureus CAP, whereas S. pyogenes was associated with a higher risk for complications (OR 8 [95%CI 1.1-57.2]) and ICU admission (OR 7.1 [95%CI 1.7-29.1]) compared with pneumococcal CAP. Conclusion. In a setting with high PCV coverage, culture-confirmed bacterial CAP did not decrease over time and there was a relative increase of S. pyogenes and S. aureus. Children with CAP caused by S. pyogenes were more likely to develop complications.